An investigation on humpback whales' distribution in relation to Antarctic sea ice in the IDCR/SOWER dataset - Mthethwa, Mbali (Department of Oceanography, 2025)
Existing literature has identified humpback whales (Megaptera novaeangliae) as climate sentinels since their feeding ecology is inextricably linked to the oceanic features around Antarctica, and to the seasonal sea ice. The changing Antarctic cryosphere in response to climate change threatens not only their habitat but also their prey resources. Understanding the interaction between the changing Antarctic Sea ice and its influence on the recovering humpback whales' distribution and behaviour is fundamental. Long-term ecological research offers the potential to understand ecological interactions and variability therein, over time scales relevant to both the life history of the animals and their physical environment. Implemented to assess the effectiveness of the moratorium on baleen whale densities, the IDCR/SOWER dataset is the sole cetacean long-term dataset containing in-depth information about the recent status of all Southern Ocean baleen whales. This study examines the potential utility of this dataset beyond its original scope, specifically assessing how it can contribute to climate research. Using the humpback whale sightings dataset, I prepared a workflow analysis to visually assess the distribution of humpback whales during the IDCR/SOWER surveys in relation to the sea ice from climate data records. The analysis was framed around the use of regional sectors typically used for sea ice research, rather than the feeding areas identified by the International Whaling Commission. The results show that although humpback whales indicate southward expansion as the sea ice retreats, the influence of interannual changes in sea ice on sightings is not uniform, and evident only in a few sectors. Taking into consideration the caveats of using presence/absence whale distribution data, this study represents a significant step forward in demonstrating the potential of this dataset for interdisciplinary research on polar environments beyond its original intention